A generalized regular form for multivariable sliding mode control. Issue 1 (2001) - Perruquetti Perruquetti, W. W.; Richard Richard, J. P. J. P.; Borne Borne, P. P.
Abstract : The paper shows how to compute a diffeomorphic state space transformation in order to put the initial mutivariable nonlinear model into an appropriate regular form . This form is an extension of the one proposed by Lukyanov and Utkin [9], and constitutes a guidance for a "natural" choice of the sliding surface. Then stabilization is achieved via a sliding mode strategy. In order to overcome the chattering phenomenon, a new nonlinear gain is introduced.